2012
DOI: 10.1002/ana.23566
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging detection of vascular reactivity in cerebral amyloid angiopathy

Abstract: Objective In addition to its role in hemorrhagic stroke, advanced cerebral amyloid angiopathy (CAA) is also associated with ischemic lesions and vascular cognitive impairment. We used functional MRI techniques to identify CAA-associated vascular dysfunction. Methods Functional MRI was performed on 25 nondemented subjects with probable CAA (mean ± standard deviation age 70.2±7.8) and 12 healthy elderly controls (age 75.3±6.2). Parameters measured were reactivity to visual stimulation (quantified as blood oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
184
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(207 citation statements)
references
References 26 publications
21
184
2
Order By: Relevance
“…0.30 for all comparisons). DISCUSSION Our data confirm 2 previous pilot studies suggesting decreased brain task-related blood flow reactivity in CAA, 3,4 and provide new evidence to suggest that the physiologic basis of the reduced signal is impaired vasodilation, not decreased metabolic activity. Additionally, our data are the first to suggest there is a gradient of increasingly impaired vasodilation from anterior (frontal) to posterior (occipital) brain regions that matches the known distribution of vascular amyloid deposition in CAA as identified pathologically 17 and on PET amyloid imaging.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…0.30 for all comparisons). DISCUSSION Our data confirm 2 previous pilot studies suggesting decreased brain task-related blood flow reactivity in CAA, 3,4 and provide new evidence to suggest that the physiologic basis of the reduced signal is impaired vasodilation, not decreased metabolic activity. Additionally, our data are the first to suggest there is a gradient of increasingly impaired vasodilation from anterior (frontal) to posterior (occipital) brain regions that matches the known distribution of vascular amyloid deposition in CAA as identified pathologically 17 and on PET amyloid imaging.…”
Section: Resultssupporting
confidence: 90%
“…To further ensure that we studied patients without significant occipital lobe neuronal dysfunction, we excluded patients with hemorrhages in the occipital pole, visual field defects, or poor visual acuity, and observed patients during the experiment to ensure that they attended well to the task. Two previous studies have found decreased occipital visual taskrelated blood flow responses in CAA and suggested they were caused by decreased vascular reactivity 3,4 ; however, the present study is the first to directly show neurovascular decoupling in patients with CAA.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…longer BOLD time to peak in patients were related to greater WMH volume, independent of age, sex, and hypertension, [88][89][90] providing a possible mechanism for subcortical ischemic injury. The authors hypothesize that impaired vasoreactivity in CAA might cause a mismatch between perfusion and metabolic demand, thereby inducing ischemic damage.…”
Section: Pathophysiologic Mechanisms Of Ischemia In Cerebral Amyloid mentioning
confidence: 94%